2019
DOI: 10.1111/jep.13291
|View full text |Cite
|
Sign up to set email alerts
|

The effects of clinical decision support systems on insulin use: A systematic review

Abstract: BackgroundA clinical decision support system (CDSS) is a computerized system using case‐based reasoning to assist clinicians in assessing disease status, in selecting appropriate therapy or in making other clinical decisions. Previous randomized controlled trials (RCTs or trials) have shown that CDSSs have the potential to improve the insulin use, but the evidence was conflicting and uncertain. The purpose of our study was to determine whether a CDSS improves the use of insulin.MethodPubMed, Embase, Cochrane C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…A number of studies have shown that CDSSs are relevant for particularly complex insulin therapy and the general management of T2DM (e.g. glycaemia control and glycated haemoglobin levels) 20–22,25 . The use of a CDSS to improve antidiabetic drug prescriptions is poorly documented, despite the fact that this drug class is often involved in preventable ADRs—mainly because of inappropriate use 31 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have shown that CDSSs are relevant for particularly complex insulin therapy and the general management of T2DM (e.g. glycaemia control and glycated haemoglobin levels) 20–22,25 . The use of a CDSS to improve antidiabetic drug prescriptions is poorly documented, despite the fact that this drug class is often involved in preventable ADRs—mainly because of inappropriate use 31 .…”
Section: Discussionmentioning
confidence: 99%
“…insulin use and glycaemia control). [20][21][22][23][24] A literature review has suggested that the use of a CDSS is associated with an overall improvement in the care process. 25 However, these studies analysed the overall management of patients with T2DM and did not focus on drug management; none of the studied outcomes was related to the appropriateness of antidiabetic drug prescriptions.…”
Section: Clinical Decision Support Systems (Cdsss) Have Been Developedmentioning
confidence: 99%
See 1 more Smart Citation
“…According to EBHC pyramid 5.0 for accessing pre-appraised evidence, CDSSs rest at the top of the pyramid, and they are designed based on information sources such as clinical practice guidelines (CPG), systematic reviews, and evidence summaries [2]. The literature shows the potential positive impact of CDSSs on physicians' decision-making [3][4][5][6][7]. However, a recent meta-analysis shows that the pooled impact of CDSSs on guideline adherence during patient care is relatively low [8].…”
Section: Introductionmentioning
confidence: 99%
“…These systems provide services ranging from simple reminders to complex risk prediction [ 3 ] and support health care providers in diagnosis, treatment decisions, and population health management. Clinical decision support systems assist one or more levels of decision making: alerting, interpreting, critiquing, assisting, diagnosing, and managing [ 4 ]. Diagnostic support systems are a subset of clinical decision support systems that are specifically designed to support clinician in diagnosing patients [ 5 ].…”
Section: Introductionmentioning
confidence: 99%